2019
DOI: 10.3390/jcm8101668
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Oral Behaviour and the High Need for Periodontal Treatment in Patients with Heart Insufficiency and after Heart Transplantation: A Need for Special Care Programs?

Abstract: Background: The aim of this cross-sectional study was the assessment of dental behaviour and oral health condition of heart transplant recipients (HTx) in comparison to patients with heart insufficiency (HI). Methods: Patients attending the Department for Cardiac Surgery, Leipzig Heart Center, Germany were recruited. Standardized questionnaires regarding dental behaviour and periodontal complaints were applied. A dental (decayed-, missing- and filled-teeth index) and periodontal examination (periodontal probin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…The high prevalence of periodontal treatment need in both groups was the main finding within oral health findings of the current study. A high periodontal treatment need in the HC is in line with similar findings of the Fifth German Oral Health Study, a representative study of German general population . This seems to be the explanation why there is no difference between LVAD and HC group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The high prevalence of periodontal treatment need in both groups was the main finding within oral health findings of the current study. A high periodontal treatment need in the HC is in line with similar findings of the Fifth German Oral Health Study, a representative study of German general population . This seems to be the explanation why there is no difference between LVAD and HC group.…”
Section: Discussionsupporting
confidence: 88%
“…However, there is still no study available that examined the recent dental care situation of patients with LVAD. A previous study by this working group was able to demonstrate a high periodontal treatment need in patients with heart insufficiency and after heart transplantation 11 . Moreover, it is still unclear whether oral diseases could be associated to driveline infections as a complication of high clinical relevance.…”
Section: Introductionmentioning
confidence: 97%
“…This could be additionally negatively influenced by the increased risk for complications of these patients during dental therapy [11,19,29,30], which might result in uncertainty of the dentist and thus in waiver of invasive (periodontal) therapy. This gap in periodontal treatment substantiates the demand of special care programs by specialized dentists with an interdisciplinary approach as demanded in literature [8,13,18].…”
Section: Discussionmentioning
confidence: 77%
“…The higher number of missing teeth in the heart diseased cohort might indicate a surgical dental rehabilitation prior to HTx, LVAD implantation or listing for potential HTx in HF group. A previous cross-sectional study of patients with HF and after HTx also showed a high periodontal treatment need of these patients [18]. Moreover, another recent cross-sectional study of Chinese HTx recipients also found high periodontal treatment need for these patients [12].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation